Pengaruh Media Puzzle Telapak Tangan Angka terhadap Kemampuan Mengenal Lambang Bilangan 1-10 pada Anak Disabilitas Intelektual Ringan Kelas IV - Haiqul Umam; Nostalgianti Citra Prystiananta; Angger Timansyah (JOEAI (Journal of Education and Instruction), 2026)
This study aims to examine the use of wooden palm-shaped puzzles with numbers on the ability to recognize number symbols 1–10 in fourth-grade children with mild intellectual disabilities at SLB C TPA Jember. The study used a nonequivalent control group pretest-posttest within a quasi-experimental framework, involving four students selected purposively. The test instrument consisted of 10 items that met quality criteria, with item-total validity values ​​ranging from 0.890–0.992 and very high reliability (Cronbach's Alpha = 0.985). Posttest results showed an increase in students' ability to recognize, name, and differentiate number symbols 1–10 after learning using the puzzles. In conclusion, wooden palm-shaped puzzles are effective as a concrete and multisensory learning medium for basic numeracy.   Keywords: Mild Intellectual Disability, Quasi-Experiment, Number Symbols, Basic Numeracy, Wooden Puzzles